Społeczne aspekty zjawisk językowych: dwa języki, jedna grupa - (:unkn) unknown (Social Studies: Theory and Practice, 2020)
Understanding of ethnic identification at the theoretical level is always complicated by the lack of a single concept of social identity. When trying to distinguish between objective and subjective criteria of social identification, their strong interrelation becomes obvious. Thus, empirical studies suggest that in a particular context, the coexistence of two models is possible. In order to find the answer during 2012 – 2019, in-depth interviews were conducted in Chernivtsi oblast. As a result, respondents aged 21-76 from Novoselytsia, Hlyboka of Chernivtsi oblast, and from the city of Chernivtsi were selected for the analysis. As a result, the vector of attention shifted towards language and linguistic identification. Taking into account the bond of Moldovan languages and cultures, it was necessary to establish the role of language in the ethnic identity Moldovans. In addition, there is a need to determine whether it is legitimate to consider a mother tongue or a “name of language” as a tool of communication and identity in a situation where two languages are highly related. The use of two names by Moldovans to denote their mother tongue – either Moldovan or Romanian – leads to several important conclusions. First of all, it is about the desire to emphasize the difference. This also correlates with the results of studies conducted in Moldova, in particular that among Moldovan population of the country, national self-identification is a difficult issue, especially at the beginning of 2000 s. However, the development of Moldovan and Romanian culture in different geopolitical areas has influenced the further identification of citizens in both countries. Kontakty międzykulturowe oraz język ojczysty odgrywają ważną rolę w kształtowaniu własnej tożsamości etnicznej. Celem badań przeprowadzonych w obwodzie Czerniowieckim na Ukrainie było ustalenie przyczyn wykorzystania przez Mołdawian dwóch języków ojczystych. Biorąc pod uwagę, że języki są niemal identyczne (według wielu badaczy jest to jeden język o różnych odmianach regionalnych), można wnioskować o używanie odmiennych „nazw” języka ojczystego. Przede wszystkim chodzi o chęć podkreślenia własnej różnicy etnicznej i kulturowej. Odpowiada to wynikom badań przeprowadzonych w Mołdawii, w szczególności o tym, że wśród ludności mołdawskiej tego kraju samoidentyfikacja narodowa jest kwestią trudną. Rozwój kultury mołdawskiej w różnych obszarach geopolitycznych (mołdawskim, czyli w obrębie wpływów rosyjskich i radzieckich, oraz rumuńskim) wpłynął na tożsamość mieszkańców. Proces kształtowania tożsamości narodowej trwa nadal. W związku z tym, w odniesieniu do bukowińskich Mołdawian uzasadnione jest twierdzenie, że istnieje wśród niektórych z nich frustracja językowa i etniczna. Przyczyny frustracji można powiązać z problemami w samej Mołdawii. Źródłem informacji o nich dla ukraińskich Mołdawian jest telewizja oraz kontakty osobiste, rodzinne, przyjacielskie ekonomiczne. Będąc krajem postradzieckim, Mołdawia często jest kojarzona z państwem, którego problemy gospodarcze i społeczne niewiele różnią się od problemów Ukrainy. Obecnie zasięg i głębokość tego zjawiska jest trudna do ustalenia, ale aspekt ten wymaga dodatkowej uwagi w dalszych badaniach. Jeśli jednak przyjrzymy się bardziej umiarkowanemu poglądowi (mianowicie, że tożsamość mołdawska jest zdeterminowana przez triadę: państwo – narodowość – język), to jest prawdopodobne, że w perspektywie średnioterminowej frustracje etniczne i językowe bukowińskich Mołdawian zostaną zredukowane do zera.
Keywords: ethnic identity, language identity, mother tongue, name of language, Moldovans in Ukraine, politization of the language process